SISTEM PENGUMUMAN AKADEMIK “REMIK” TERINTEGRASI BERBASIS ANDROID - Mina Ismu Rahayu; Ari Subagja (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2015)
Integrated academic notification system is a system which is designed to fulfill student's need in collectingimportant information in form of academic notification which related to student's activity in collegeenvironment. Language variety of notification has to be short, clear and dense. The main problems facedin the delivery of the announcement is still in the conventional manner or by way of social mediaannounced through facebook. The methodology of software development uses waterfall method insolving the problem which emerge in the process of academic notification system. Therefore, the designedacademic notification system consists of two important parts, namely web server which manage the datathat will be displayed and android application as media output. This application uses Code Igniter (CI)framework in its webserver, while android uses Phonegap and Angular JS framework which is createdby using language code of HTML 5, Javascript, CSS, and data exchange between android and webserverusing JSON. The testing indicated that The designed notification produces output in form of notificationor reminder. All the manual process will be facilitated using computerization process. Keywords: Phonegap, Announcement, Notification, Android